Leverage, Ukuran Perusahaan, Gross Profit Margin, dan Current Ratio terhadap Harga Saham pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi - Mei Kristanty Nababan; Mahmuddin Syah Lubis (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of variable leverage, firm size, gross profit margin, and current ratio on stock prices. This research method is descriptive quantitative. The population of this study obtained 54 companies selected using purposive sampling through certain criteria as many as 24 companies multiplied by five years to 120. Data analysis used multiple linear analysis using F test, T test, and coefficient of determination. The results showed that the value of Fcount> Ftable was 9.727> 2.45. The results of the T test show, a) the leverage variable has a value of tcount < ttable, namely 0.535 <f1.65810; b) the DER variable has a value of tcount < t table that is 0.078 < 1.65810 with a significant level of 0.938> 0.05; c) the GPM variable has tcount> ttable that is 5,955>1,65810. In conclusion, partially shows that gross profit margin has a significant effect on stock price audits. Meanwhile, leverage, firm size, and current ratio have no significant effect on stock prices and firm age. Simultaneously shows that leverage, company size, gross profit margin and current ratio have an effect on stock prices. Keywords: Current Ratio, Gross Profit Margin, Stock Price, Leverage, Company Size